Reativação do citomegalovírus em pacientes graves aumenta a mortalidade - Sousa, Estefânia Conceição Carmo (2024)
INTRODUCTION: In critically ill patients, cytomegalovirus (CMV) frequently reactivates. This reactivation is linked to extended hospital and ICU stays, increased need for mechanical ventilation, and higher incidences of sepsis, healthcare-associated infections (HAIs), morbidity and mortality. OBJECTIVES: This study to describe CMV reactivation and outcomes in patients treated at or admitted to a university hospital. METHODS: We conducted a retrospective cohort study of patients with suspected CMV reactivation treated at a university hospital in Central Brazil from November 2021 to July 2023. Data were abstracted from medical charts and entered a form prepared in EpiData Entry software version 3.1(//www.epidata.dk/) for statistical analysis. RESULTS: Among one hundred patients with clinical suspicion of CMV reactivation by the attending medical team, thirty-one cases (31.0%) had detectable viral load in blood samples. In patients with CMV reactivation, mortality reached 19.35%, compared to 5.8% in patients with undetectable viral load (p= 0.045). Mortality and CMV reactivation were significantly (p<0.050) higher in patients infected with the human immunodeficiency virus (HIV), those with shock or healthcare-associated infections (HAIs), and those requiring mechanical ventilation (MV). Patients with suspected CMV reactivation who were treated with ganciclovir had a significantly higher mortality (25.0%) than those who did not use ganciclovir (6.25%) (p=0.025). CONCLUSIONS: CMV reactivation, HIV infection, shock, MV, and HAIs were associated with increase patient mortality. However, further studies on the use of antivirals for treatment or prophylaxis of CMV reactivation in non-transplant critically ill patients are necessary, as ganciclovir may be toxic.